ANTIOXIDANT AND ANTI-INFLAMMATORY ACTIVITIES FROM ETHANOL EXTRACT OF Eucheuma cottonii FROM LEMUKUTAN ISLAND WATERS WEST KALIMANTAN - Mega Sari Juane Sofiana; Ikha Safitri; Warsidah Warsidah; Shifa Helena; Sy Irwan Nurdiansyah (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2021)
Free radicals contribute to human health problem resulting in various human diseases, including central nervous system injury, cancer, inflammations, and the decrease of organ function related to oxidation. This condition has encouraged the effort of finding new natural antioxidant and anti-inflammatory sources. Macroalgae act as excellent natural resources due to their bioactive potential with diverse applications in various fields. Eucheuma cottonii belonging to Rhodophyceae grow abundantly along Lemukutan Island waters, however, their existence has not been exploited. This study aims to evaluate antioxidant and anti-inflammatory activities of ethanol extract of E. cottonii from Lemukutan Island waters, West Kalimantan. The observation of antioxidant activity was done using the method of DPPH (1,1-diphenyl-2-picrylhydrazyl) with UV-vis spectrophotometer, while anti-inflammatory acyivity activity was determined using the RBCs membrane stability method. The ethanolic extract of E. cottonii had potential antioxidant activity with IC50 of 127.75 ppm and was classified as moderate category. Extracts showed also anti-inflammatory acyivity activity with the concentration of 219.83 ppm. Red macroalgae E. cottonii can be used as potential natural antioxidant and anti-inflammatory agent.